Capital Structure Policy: The Moderating Role of Equity Market Timing on Profitability and Growth Opportunity - Dessy Adelin; Jonnardi Jonnardi; Sakdiah Binti Md Amin; Primadonna Ratna Mutumanikam (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This research endeavors to investigate how profitability and growth opportunities shape firms’ capital structure decisions, while also elucidating the moderating influence of equity market timing (EMT) within these associations. The inquiry centers on coal mining enterprises—an industry distinguished by capital-intensive operations and pronounced sensitivity to market fluctuations.Methodology: Adopting a quantitative paradigm, this study utilizes panel data drawn from 23 coal mining firms listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The sample is determined through purposive selection. Moderated regression analysis serves to assess the interplay between profitability, growth opportunities, and capital structure, with EMT incorporated as a moderating construct. All variables are operationalized through financial ratios and processed using EViews software to ensure analytical rigor.Finding: Empirical evidence discloses a significant inverse nexus between profitability and capital structure, signifying that more profitable entities exhibit a diminished proclivity toward debt financing, favoring internally generated funds instead. Conversely, growth opportunities manifest a positive and significant relationship with leverage, implying that firms with broader expansion prospects are predisposed to augment their indebtedness. Moreover, EMT intensifies these dual tendencies—fortifying the adverse link between profitability and leverage while concurrently amplifying the positive association between growth opportunities and debt usage.Conclusion: Collectively, the findings underscore that capital structure formation is not solely contingent upon internal financial attributes such as profitability and growth potential but is equally sculpted by external capital market conditions. Firms, therefore, appear to recalibrate their financing configurations strategically, navigating between internal performance dynamics and the temporal advantages presented by favorable market valuations.